TRAINING OF CHOKING FIRST-AID FOR TODDLERS AFFECTING MOTHERS' KNOWLEDGE LEVEL AT INTEGRATED HEALTHCARE CENTER - Khodijah Khodijah; Deni Irawan; Nur Aida Perdani (Siklus : Journal Research Midwifery Politeknik Tegal, 2021)
Choking is the leading cause of mortality and disability in toddlers under three years or younger. In 1999 – 2017, 114 deaths occurred to children aged 1 – 4 years in the USA because of choking on food and unusual objects. The family's ignorance in choking first aid was also one of the reasons for mortality in toddlers. The research aimed to determine the effect on the training of choking first aid for toddlers towards mothers' knowledge level at Integrated Healthcare Center Debong Tengah sub-district. It was a quantitative study with a quasi-experimental design using One Group Pretest-Posttest. It used quota sampling and obtained 39 respondents. Wilcoxon Signed Ranks Test showed that p-value 0.0001 (p0.05) meant that there is an effect from the training of choking first aid for toddlers towards mothers' knowledge level. It is also proven by the improvement of the mothers' knowledge before and after getting the training. It is expected that the mothers can apply the knowledge that they have got during the training if their toddlers need choking first aid.Keywords: first aid training, knowledge, choking